Psychosocial issues in people with epilepsy in Togo and Benin (West Africa) II: quality of life measured using the QOLIE-31 scale - Nubukpo, Philippe; Clément, Jean-Pierre; Houinato, Dismand; Radji, A.; Grunitzky, E. K.; Avodé, G.; Preux, Pierre-Marie (My University, 2004)
PURPOSE: This study in Togo and Benin, West Africa, was aimed at measuring health-related quality of life (HRQOL) of people with epilepsy (PWE). METHODS: It was a cross-sectional study among 281 adult PWE in Togo and 215 in Benin matched with the same number of controls without epilepsy, using the Quality Of Life in Epilepsy Scale-31 (QOLIE-31). RESULTS: In Togo and Benin, controls had significantly better HRQOL (80.3+/-7.4, 72.2+/-12.7) than PWE (49.5+/-14.4, 52.1+/-33.4) according to the QOLIE-31 Overall score (P<0.0001). HRQOL was, in general, negatively correlated with a higher frequency of seizures and lack of treatment. CONCLUSION: Results call for specific management of epilepsy in PWE in Togo and Benin to improve their HRQOL.
Keywords: Psychosocial; epilepsy; Togo and Benin